Psychosomatic peculiarities of lipomas course in the maxillofacilal area - Dzhereley, A A; Romanenko, I G; Kryuchkov, D Yu; Gorobets, S M (Journal of Education, Health and Sport, 2015)
Dzhereley A. A., Romanenko I. G., Kryuchkov D. Yu., Gorobets S. M. Psychosomatic peculiarities of lipomas course in the maxillofacilal area. Journal of Education, Health and Sport. 2015;5(7):163-170. ISSN 2391-8306. DOI 10.5281/zenodo.19470 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A163-170 https://pbn.nauka.gov.pl/works/579617 http://dx.doi.org/10.5281/zenodo.19470 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. Psychosomatic peculiarities of lipomas course in the maxillofacilal area Dzhereley A. A., Romanenko I. G., Kryuchkov D. Yu., Gorobets S. M. Federal State Autonomous Educational Institution of Higher Education "Crimean Federal University named after V.I. Vernadskiy" Medical Academy named after S.I.Georgievsiy Dentistry Department Summary Patients with lipomas in the maxillofacial area show some types of psychological reactions. But the most focused attention of the doctor in the postoperative period is required by the patients of euphoric-anosognosic psychosomatic group due to the high level of compliance between psychological reactions and somatic indicators. Was determined of three psychosomatic groups: anxiety-obsessive-phobic, euphoric-anosognosic and harmonious. The most focused attention of the doctor in the postoperative period is required by the patients of euphoric-anosognosic psychosomatic group due to the high level of compliance. Keywords: lipomas, maxillofacial area, psychological reactions, postoperative period.